2018
DOI: 10.1111/jpy.12769
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Phyllonema (Rivulariaceae, Cyanobacteria) with an emendation of the genus

Abstract: Two untapered, heterocytous species were observed and collected from the intertidal and supratidal zones of the Mexican coastline of the Pacific Ocean near Oaxaca and from the Gulf of Mexico. These populations were highly similar in morphology to the freshwater taxon Petalonema incrustans in the Scytonemataceae. However, 16S rRNA sequence data and phylogenetic analysis indicated that they were sister taxa to the epiphyllic, Brazilian species Phyllonema aveceniicola in the Rivulariaceae, described from culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…The species in Crocosphaera are fairly cryptic, and we rely on percent dissimilarity based on aligned ITS sequences to other species in the genus as one of the major criteria for species recognition. This follows precedents set in a number of cyanobacterial taxonomy papers (Erwin and Thacker 2008, Osorio-Santos et al 2014, Bohunick a et al 2015a, Gonz alez-Resendiz et al 2018a,b, Mai et al 2018, V azquez-Mart ınez et al 2018. These papers have shown that there is generally a marked discontinuity between percent dissimilarity within species (<3.0%) and percent dissimilarity between species (>7.0%).…”
Section: Discussionmentioning
confidence: 58%
“…The species in Crocosphaera are fairly cryptic, and we rely on percent dissimilarity based on aligned ITS sequences to other species in the genus as one of the major criteria for species recognition. This follows precedents set in a number of cyanobacterial taxonomy papers (Erwin and Thacker 2008, Osorio-Santos et al 2014, Bohunick a et al 2015a, Gonz alez-Resendiz et al 2018a,b, Mai et al 2018, V azquez-Mart ınez et al 2018. These papers have shown that there is generally a marked discontinuity between percent dissimilarity within species (<3.0%) and percent dissimilarity between species (>7.0%).…”
Section: Discussionmentioning
confidence: 58%
“…2014a, González‐Resendiz et al. ,b) is in the ambiguous range of 0.055 < P < 0.065 (Table ), indicating that the process of speciation is still underway based on this recognition criterion.…”
Section: Discussionmentioning
confidence: 98%
“…Since that time, several authors have used the percent dissimilarity criterion to assist in defining species (Pietrasiak et al 2014;Bohunická et al 2015;Johansen et al 2017;Shalygin et al 2017;Vazquez-Martínez et al 2018;Mai et al 2018;Becerra-Absalón et al 2018;González-Resendiz et al 2018a, 2018bMareš et al 2019;Pietrasiak et al 2019). These authors all found a clear discontinuity between interspecies dissimilarity and intraspecies dissimilarity consistent with both Erwin & Thacker (2008) and Osorio-Santos et al (2014).…”
Section: Discussionmentioning
confidence: 99%